2007
DOI: 10.1093/pasj/59.3.615
|View full text |Cite
|
Sign up to set email alerts
|

The IRSF Magellanic Clouds Point Source Catalog

Abstract: We present a near-infrared ($JHK_{\rm s}$) photometric catalog, including 14811185 point sources for a 40 deg$^2$ area of the Large Magellanic Cloud, 2769682 sources for an 11 deg$^2$ area of the Small Magellanic Cloud, and 434145 sources for a 4 deg$^2$ area of the Magellanic Bridge. The 10$\sigma$ limiting magnitudes are 18.8, 17.8, and 16.6 mag at $J, H$, and $K_{\rm s}$, respectively. The photometric and astrometric accuracies for bright sources are 0.03–0.04 mag and 0$\rlap {.}{^{\prime\prime}}$1, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(111 citation statements)
references
References 24 publications
5
104
1
1
Order By: Relevance
“…Standard stars from Persson et al (1998) were observed on each night and the results presented here are on the natural system of the SIRIUS camera, but with the zero-point of the Persson et al standards. These magnitudes are expected to be close to those on the Two Micron All Sky Survey (2MASS) system (Kato et al 2007). The field of view is 7.8 × 7.8 arcmin 2 , but this is reduced to 7.2 × 7.2 arcmin 2 during the course of the reductions.…”
Section: O B S E Rvat I O N Ssupporting
confidence: 54%
“…Standard stars from Persson et al (1998) were observed on each night and the results presented here are on the natural system of the SIRIUS camera, but with the zero-point of the Persson et al standards. These magnitudes are expected to be close to those on the Two Micron All Sky Survey (2MASS) system (Kato et al 2007). The field of view is 7.8 × 7.8 arcmin 2 , but this is reduced to 7.2 × 7.2 arcmin 2 during the course of the reductions.…”
Section: O B S E Rvat I O N Ssupporting
confidence: 54%
“…Bonanos et al (2009Bonanos et al ( , 2010 took advantage of the new data and compiled catalogs by starting with all massive stars in the LMC and SMC with high quality spectral classifications, and then matching them to entries in the Spitzer and other photometric data bases. The catalogs contain U , B, V , and I from various sources and JHK photometry (primarily from the Two Micron All Sky Survey, 2MASS; Skrutskie et al 2006 and the targeted IRSF survey, (Kato et al 2007) In this paper, we concentrate on a sub-sample of the Bonanos et al (2009Bonanos et al ( , 2010 catalogs, namely those O stars which are also in the Blair et al (2009) FUSE sample. This will allow direct comparison of results derived from different diagnostics in many cases.…”
Section: The Sample and Datamentioning
confidence: 99%
“…The USNO-B1 catalog source has R1, B2, and R2 plate magnitudes of 17.76, 21.46, and 18.9 mag, respectively. The IRSF Magellanic Cloud point source catalog (Kato et al 2007) has a source with J and H magnitudes of 18.37 ± 0.07 and  18.62 0.25 mag, respectively. The last source is from the Guide Star Catalog (V2.3) which has red, green and 0.8 μm photographic band magnitudes of 18.54, 17.69 and 18.52, respectively.…”
Section: Nova Positionmentioning
confidence: 99%